We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
159
2
avatar+133 

Compute
\(\sum_{n = 1}^{9999} \frac{1}{(\sqrt{n} + \sqrt{n + 1})(\sqrt[4]{n} + \sqrt[4]{n + 1})}.\)

 Jun 7, 2019

Best Answer 

 #2
avatar+7761 
+3

This sum is obviously telescoping :)

\(\begin{array} {rll} \phantom{=}&\displaystyle\sum^{9999}_{n=1}\dfrac{1}{\left(\sqrt{n}+\sqrt{n+1}\right)\left(\sqrt[4]{n}+\sqrt[4]{n+1}\right)}\\ =&\displaystyle \sum^{9999}_{n=1}\dfrac{\color{red}{\sqrt[4]{n+1}-\sqrt[4]{n}}}{\left(\sqrt{n}+\sqrt{n+1}\right)\left(\sqrt[4]{n}+\sqrt[4]{n+1}\right)\color{red}{\left(\sqrt[4]{n+1}-\sqrt[4]{n}\right)}}\\ =&\displaystyle \sum^{9999}_{n=1}\dfrac{\sqrt[4]{n+1}-\sqrt[4]{n}}{\left(\sqrt{n}+\sqrt{n+1}\right)\left(\sqrt{n+1}-\sqrt{n}\right)}\\ =&\displaystyle \sum^{9999}_{n=1}\dfrac{\sqrt[4]{n+1}-\sqrt[4]{n}}{n+1 - n}\\ =&\displaystyle \sum^{9999}_{n=1}\left(\sqrt[4]{n+1}-\sqrt[4]{n}\right)\\ =&\displaystyle (\color{blue}{\sqrt[4]{2}}\color{black} - \sqrt[4]1) + (\color{green}{\sqrt[4]{3}}\color{black} - \color{blue}\sqrt[4]2\color{black}) + (\sqrt[4]4 - \color{green}\sqrt[4]3\color{black}) + \cdots+(\sqrt[4]{10000}-\sqrt[4]{9999})\\ =&\displaystyle \sqrt[4]{10000} - \sqrt[4]1\\ =&\displaystyle 10 - 1\\ =& 9 \end{array}\)

.
 Jun 7, 2019
 #1
avatar
+2

sum_(n=1)^9999 1/((sqrt(n) + sqrt(n + 1)) (n^(1/4) + (n + 1)^(1/4)))≈9.000000000000000000000000000000000000000

 Jun 7, 2019
 #2
avatar+7761 
+3
Best Answer

This sum is obviously telescoping :)

\(\begin{array} {rll} \phantom{=}&\displaystyle\sum^{9999}_{n=1}\dfrac{1}{\left(\sqrt{n}+\sqrt{n+1}\right)\left(\sqrt[4]{n}+\sqrt[4]{n+1}\right)}\\ =&\displaystyle \sum^{9999}_{n=1}\dfrac{\color{red}{\sqrt[4]{n+1}-\sqrt[4]{n}}}{\left(\sqrt{n}+\sqrt{n+1}\right)\left(\sqrt[4]{n}+\sqrt[4]{n+1}\right)\color{red}{\left(\sqrt[4]{n+1}-\sqrt[4]{n}\right)}}\\ =&\displaystyle \sum^{9999}_{n=1}\dfrac{\sqrt[4]{n+1}-\sqrt[4]{n}}{\left(\sqrt{n}+\sqrt{n+1}\right)\left(\sqrt{n+1}-\sqrt{n}\right)}\\ =&\displaystyle \sum^{9999}_{n=1}\dfrac{\sqrt[4]{n+1}-\sqrt[4]{n}}{n+1 - n}\\ =&\displaystyle \sum^{9999}_{n=1}\left(\sqrt[4]{n+1}-\sqrt[4]{n}\right)\\ =&\displaystyle (\color{blue}{\sqrt[4]{2}}\color{black} - \sqrt[4]1) + (\color{green}{\sqrt[4]{3}}\color{black} - \color{blue}\sqrt[4]2\color{black}) + (\sqrt[4]4 - \color{green}\sqrt[4]3\color{black}) + \cdots+(\sqrt[4]{10000}-\sqrt[4]{9999})\\ =&\displaystyle \sqrt[4]{10000} - \sqrt[4]1\\ =&\displaystyle 10 - 1\\ =& 9 \end{array}\)

MaxWong Jun 7, 2019

18 Online Users

avatar
avatar
avatar